An ancestral bacterial division system is widespread in eukaryotic mitochondria - Leger, Michelle M; Petrů, Markéta; Žárský, Vojtěch; Eme, Laura; Vlček, Čestmír; Harding, Tommy; Lang, B Franz; Eliáš, Marek; Doležal, Pavel; Roger, Andrew J (Proceedings of the National Academy of Sciences of the United States of America, 2015)
Bacterial division initiates at the site of a contractile Z-ring composed of polymerized FtsZ. The location of the Z-ring in the cell is controlled by a system of three mutually antagonistic proteins, MinC, MinD, and MinE. Plastid division is also known to be dependent on homologs of these proteins, derived from the ancestral cyanobacterial endosymbiont that gave rise to plastids. In contrast, the mitochondria of model systems such as Saccharomyces cerevisiae, mammals, and Arabidopsis thaliana seem to have replaced the ancestral α-proteobacterial Min-based division machinery with host-derived dynamin-related proteins that form outer contractile rings. Here, we show that the mitochondrial division system of these model organisms is the exception, rather than the rule, for eukaryotes. We describe endosymbiont-derived, bacterial-like division systems comprising FtsZ and Min proteins in diverse less-studied eukaryote protistan lineages, including jakobid and heterolobosean excavates, a malawimonad, stramenopiles, amoebozoans, a breviate, and an apusomonad. For two of these taxa, the amoebozoan Dictyostelium purpureum and the jakobid Andalucia incarcerata, we confirm a mitochondrial localization of these proteins by their heterologous expression in Saccharomyces cerevisiae. The discovery of a proteobacterial-like division system in mitochondria of diverse eukaryotic lineages suggests that it was the ancestral feature of all eukaryotic mitochondria and has been supplanted by a host-derived system multiple times in distinct eukaryote lineages.
Keywords: mitochondria; Mitochondria; sekvence nukleotidů; adenosintrifosfatasy; Bacterial Proteins; Dictyostelium; Arabidopsis; fylogeneze; MinCDE; Saccharomyces cerevisiae; Phylogeny; Cytoskeletal Proteins; Bacteria; molekulární sekvence - údaje; Databases, Genetic; molekulární evoluce; Evolution, Molecular; cytoskeletální proteiny; buněčné dělení; mitochondrial division; pravděpodobnostní funkce; proteiny buněčného cyklu; Likelihood Functions; databáze genetické; DNA, Bacterial; proteiny z Escherichia coli; DNA bakterií; Cell Division; Escherichia coli Proteins; Plastids; Adenosine Triphosphatases; Min proteins; plastidy; bakteriální proteiny; Mitochondrial Dynamics; Molecular Sequence Data; Base Sequence; mitochondrial fission; Cell Cycle Proteins; mitochondrie; mitochondriální dynamika